Molecular markers for analyses of intraspecific genetic diversity in the Asian Tiger mosquito, Aedes albopictus - Manni,M.U. (BioMed Central, 2015)
© 2015 Manni et al.; licensee BioMed Central. Background: The dramatic worldwide expansion of Aedes albopictus (the Asian tiger mosquito) and its vector competence for numerous arboviruses represent a growing threat to public health security. Molecular markers are crucially needed for tracking the rapid spread of this mosquito and to obtain a deeper knowledge of population structure. This is a fundamental requirement for the development of strict monitoring protocols and for the improvement of sustainable control measures. Methods: Wild population samples from putative source areas and from newly colonised regions were analysed for variability at the ribosomal DNA internal transcribed spacer 2 (ITS2). Moreover, a new set of 23 microsatellite markers (SSR) was developed. Sixteen of these SSRs were tested in an ancestral (Thailand) and two adventive Italian populations. Results: Seventy-six ITS2 sequences representing 52 unique haplotypes were identified, and AMOVA indicated that most of their variation occurred within individuals (74.36%), while only about 8% was detected among populations. Spatial analyses of molecular variance revealed that haplotype genetic similarity was not related to the geographic proximity of populations and the haplotype phylogeny clearly indicated that highly related sequences were distributed across populations from different geographical regions. The SSR markers displayed a high level of polymorphism both in the ancestral and in adventive populations, and F ST estimates suggested the absence of great differentiation. The ancestral nature of the Thai population was corroborated by its higher level of variability. Conclusions: The two types of genetic markers here implemented revealed the distribution of genetic diversity within and between populations and provide clues on the dispersion dynamics of this species. It appears that the diffusion of this mosquito does not conform to a progressive expansion from the native Asian source area, but to a relatively recent and chaotic propagule distribution mediated by human activities. Under this scenario, multiple introductions and admixture events probably play an important role in maintaining the genetic diversity and in avoiding bottleneck effects. The polymorphic SSR markers here implemented will provide an important tool for reconstructing the routes of invasion followed by this mosquito.